Analisisi Analisis Potensi Penerapan Metode 3R di Kampung Sebelang Kecamatan Muara Pahu Kabupaten Kutai Barat Tahun 2022: Analisis Potensi Penerapan Metode 3R di Kampung Sebelang Kecamatan Muara Pahu Kabupaten Kutai Barat Tahun 2022 - Rinda Suryani nda; Apriyani; Iwan Harwidian Maharisma (Universitas Widya Gama Mahakam Samarinda, 2023)
ABSTRACT Suryani, Rinda. Analysis of the Potential Application of the 3R Method in Kampung Sebelang, Muara Pahu District, West Kutai Regency in 2022, under the guidance of Apriyani, SKM, MPH as advisor I and Iwan Harwidian Maharisma, S.Pi, M.Si as advisor II. Waste is one of the environmental problems that require serious attention. The existence of household waste in an environment is due to waste management which is still dominated by the system of collecting, transporting the waste, and disposing of to the final processing site (TPA), the purpose of this study is to analyze the behavior of the people of Kampung Sebelang in household waste management, analyze the application of the concept of household waste management with the 3R method in Kampung Sebelang and analyze the role of Puskesmas (Public Health) in carrying out guidance and supervision of garbage management in Kampung Sebelang. The qualitative Research Method is a research method carried out with the main objective purpose of providing an overview or description of a situation or phenomenon objectively through in-depth interviews with 15 informants, 3 Key Informants, namely 2 Implementing Sanitarians and 1 DLH, 3 RT Chairman and 9 people of Kampung Sebelang. The results of the study describe the condition of waste management carried out by the community in Kampung Sebelang through being burned, thrown in rivers, stockpiled, and becoming animal feed. To develop environmentally friendly waste management, the people of Kampung Sebelang are interested in being able to apply the concept of waste management with the 3R method. Puskesmas as part of the government has a role in educating and assisting as well as supervising in realizing environmentally friendly waste management with a 3R method. Keywords : Household Waste, Waste management with 3R method